Energy Poverty and Subjective Well-Being in China: New Evidence from the China Family Panel Studies - Peng Nie; Qiaoge Li; Alfonso Sousa-Poza (Institute of Labor Economics (IZA), 2021)
Using the 2012-2018 waves of the China Family Panel Studies, we investigate the impact of energy poverty (EP) on subjective well-being (SWB) among Chinese adults aged 18 and over. In addition to documenting EP rates in the range of 13.2% to 35.3% (dependent on measurement used), we show that EP lowers life satisfaction, with more pronounced impacts among males, the poor, and those residing in central regions. These results are robust to both alternative EP and SWB measures and to a series of estimation approaches that control for endogeneity. An additional structural equation modelling analysis of underlying mechanisms confirms that individual self-reported health, housing quality, and household food expenditure mediate the EP-SWB relation.
Keywords: I10; I12; R21; 330; energy poverty; life satisfaction; happiness; depression; China